1999
DOI: 10.1300/j087v32n01_02
|View full text |Cite
|
Sign up to set email alerts
|

Agreement, Maintenance, Satisfaction and Relitigation in Mediated and Non-Mediated Custody Cases

Abstract: Data from 169 mediated cases and 61 non-mediated cases from a County Court Custody Mediation Program were analyzed in terms of incidence of agreement, long-term maintenance of agreement, disputant satisfaction with process and outcome, and rates of relitigation or recidivism. It was hypothesized that mediated cases would have high rates of agreement and high rates of agreement maintenance; that disputants in mediated cases would be more satisfied than disputants in non-mediated cases; and, that mediated cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
0
16
0
2
Order By: Relevance
“…Furthermore, we found that parents were more satisfied with mediation than with adversary settlement six weeks after dispute resolution (Emery & Wyer, 1987b; Emery, Matthews, & Wyer, 1991), a year and a half later (Emery, Matthews, & Kitzmann, 1994), and twelve years following the initial settlement (Emery et al, 2001). Many other researchers report finding greater satisfaction with mediation in comparison to adversary settlement, and in general, parties report a high degree of satisfaction with mediation (Beck & Sales, 2001; Jones & Bodtker, 1999; Kelly, 1996). Thus, we are confident that mediation produces higher levels of satisfaction than adversary methods based on our own findings and those of others.…”
Section: Empirically Comparing Mediation and Adversary Settlementmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, we found that parents were more satisfied with mediation than with adversary settlement six weeks after dispute resolution (Emery & Wyer, 1987b; Emery, Matthews, & Wyer, 1991), a year and a half later (Emery, Matthews, & Kitzmann, 1994), and twelve years following the initial settlement (Emery et al, 2001). Many other researchers report finding greater satisfaction with mediation in comparison to adversary settlement, and in general, parties report a high degree of satisfaction with mediation (Beck & Sales, 2001; Jones & Bodtker, 1999; Kelly, 1996). Thus, we are confident that mediation produces higher levels of satisfaction than adversary methods based on our own findings and those of others.…”
Section: Empirically Comparing Mediation and Adversary Settlementmentioning
confidence: 94%
“…We did find a trend for greater compliance with child support orders among nonresidential parents who mediated, although noncompliance was quite high in both groups (Emery, Matthews, & Kitzmann, 1994). Others also have found higher rates of compliance with various aspects of separation agreements (Irving & Benjamin, 1992; Irving, Benjamin, Bohm, & MacDonald, 1981; Kelly, 1990; Pearson & Thoennes, 1989), although the evidence is somewhat mixed and parents who mediate may actually use court services more often (Jones & Bodtker, 1999). We suggest, however, that repeated use of court services may be a positive, not a negative, outcome for mediation.…”
Section: Empirically Comparing Mediation and Adversary Settlementmentioning
confidence: 99%
“…After mediation was completed, members of the Emery research team visited each family's home, where the structured interview took place and self-report questionnaires were completed. Other studies such as Jones and Bodtker (1999) and Meyer (1992) used archival court record data to identify mediation and litigation participants and mailed self-report questionnaires to them. As for Marcus, Marcus, Stilwell, and Doherty (1999), who were interested in comparing mediation and litigation groups just…”
Section: Characteristics Of Individual Studies As Seen Inmentioning
confidence: 99%
“…As indicated in Table 1, studies either included all divorce issues in mediation or limited mediation to only childrelated issues such as custody. Specifically, Kelly (1989) and Marcus, Marcus, Stilwell, and Doherty (1999) used all-inclusive mediation while Emery, Matthews, and Wyer (1991); Jones and Bodtker (1999); and Meyer (1992) limited mediation to child-related issues.…”
Section: Characteristics Of Individual Studies As Seen Inmentioning
confidence: 99%
“…In addition, families who enter into mediation tend to have fewer custody hearings (Emery, Matthews, & Wyer, 1991). Mediated disputed custody cases had histories of greater involvement in the court system, however when mediation occurred, the consequence was reduced to relitigation (Jones & Bodtker, 1999). Not all findings regarding mediation have been positive.…”
Section: The Use Of Mediation In Contested Divorcementioning
confidence: 99%